Noonan syndrome males display Sertoli cell-specific primary testicular insufficiency. Issue 6 (December 2018) - Moniez, Sophie; Pienkowski, Catherine; Lepage, Benoit; Hamdi, Safouane; Daudin, Myriam; Oliver, Isabelle; Jouret, Béatrice; Cartault, Audrey; Diene, Gwenaelle; Verloes, Alain; Cavé, Hélène; Salles, Jean-Pierre; et al.
Abstract : Context: Abnormalities in the hypothalamo–pituitary–gonadal axis have long been reported in Noonan syndrome (NS) males with only few data available in prepubertal children. Objective: The aim of this study was to describe the gonadal function of NS males from childhood to adulthood. Design: It is a retrospective chart review. Patients and methods: A total of 37 males with a genetically confirmed diagnosis of NS were included. Clinical and genetic features, as well as serum hormone levels (LH, FSH, testosterone, anti-Müllerian hormone (AMH), and inhibin B) were analysed. Results: Of the 37 patients, 16 (43%) children had entered puberty at a median age of 13.5 years (range: 11.4–15.0 years); age at pubertal onset was negatively correlated with BMI SDS ( r = −0.541; P = 0.022). In pubertal boys, testosterone levels were normal suggesting a normal Leydig cell function. In contrast, NS patients had significant lower levels of AMH (mean SDS: −0.6 ± 1.1; P = 0.003) and inhibin B (mean SDS: −1.1 ± 1.2; P < 0.001) compared with the general population, suggesting a Sertoli cell dysfunction. Lower AMH and inhibin B levels were found in NS-PTPN11 patients, whereas these markers did not differ from healthy children in SOS1 patients. No difference was found between cryptorchid and non-cryptorchid patients for AMH and inhibin B levels ( P = 0.43 and 0.62 respectively). Four NS-PTPN11 patients had a severe primary hypogonadism with azoospermia/cryptozoospermia. Conclusions: NS males display Sertoli cell-specific primary testicular insufficiency, whereas Leydig cell function seems to be unaffected.